Fatores críticos de sucesso no desenvolvimento de produtos de empresas de base tecnológica incubadas - Padrão, Luís Carlos (2011)
This thesis aims at analysing the influence of incubator’s marketing support and entrepreneurial orientation of the firms on the new product development process of incubated technologically-based firms. In order to analyse this process, a model of product development for technologically-based firms was developed from a base model, which was improved regarding the definition and measurement of some of its constructs and to which the influence of the two factors above were included. The developed model was operationalized by a structural equation model. The research methodology is a survey where pretested scales were applied to measure the constructs. The target population is technologically-based firms developed in technological incubators in Brazil, the response rate was 63%, respondents represent incubators in all regions of Brazil and 22 high-tech sectors. This research presents academic and managerial contributions. Among the academic contributions, it was found empirical evidence about the relationship between incubators’ marketing support and firms’ marketing synergy, however, this support does not change accordingly to the uncertainty of the business environment of the firms, which should happen because the entrepreneurs need more support to make decisions in a high uncertainty environment. Another contribution was the empirical evidence that the way entrepreneurs align their business according to the turbulence of environment contradicts to some previous studies, specifically in relation to the degree of product innovation and marketing synergy. In relation to the degree of product innovation, the results show that in a low uncertainty environment there is a higher correlation between entrepreneurial orientation and the degree of product innovation, according to previous studies this should happen in high uncertainty environment where the clients are not able to specify precisely product’s requirements, so there are more opportunities for the firms to develop innovative products. In relation to the marketing synergy, the results show that in a high uncertainty environment there is a higher correlation between entrepreneurial orientation and marketing synergy, according to previous studies this should happen in low uncertainty environment where the clients are able to define clearly product’s requirements, which are often incremental innovations. Among the managerial contributions, the research provides a comprehensive view of the number of technology-based firms per geographical region and per sector, which enables the identification of high-tech sectors where there are not so many firms, so such sectors can be good opportunities to develop new firms. Besides, the research allows entrepreneurs to assess their positioning in relation to other firms in the same sector about the product development time and sales growth rate. The research will also provide to incubator managers an assessment of their marketing support in relation to that of other incubators in Brazil.